Study protocol of sleep disorders in cancer patients of a reference hospital in Minas Gerais – cross-sectional observational study - Pasqualotto, Luísa Teixeira; Santos, Walquíria da Mata; Santos, Cíntia Aparecida; Vieira, Sarah Cristina; Martins, Layra Fernanda; Alves, Jacqueline; Brandão, Rubia Lima; Fideles, Elisa Faccion Cruz; Pacheco, Camila Mariângela; Júnior, Newton Santos de Faria (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Sleep disorders are increasingly recognized as an important cause of morbidity and mortality. The poor quality of sleep is among the most frequent problems which patients with cancer have during treatment. Objectives: To verify the prevalence of sleep disorders in cancer patients attended at a reference hospital in the Center-West of Minas Gerais, Brazil. Methods: This research will be a cross-sectional observational study carried out by teachers and students from University of the State of Minas Gerais – UEMG, Divinópolis Unit, with subjects recruited from a reference hospital in the Center-West of Minas Gerais from March 2018 and February 2019. These patients will be evaluated clinically and will respond to Pittsburgh Sleep Quality Index (PSQI), Insonnia Severity Index (ISI), Epworth Sleepiness Scale (ESS), Berlin Questionnaire, European Organization for Research and Treatment of Cancer core Quality of life Questionnaire (EORTHC QLQ-30) and Beck Anxiety and Depression Inventory, respectively, assessing sleep quality, presence of sleep disorders, severity and presence of insomnia, excessive daytime sleepiness, risk for obstructive sleep apnea, quality of life and levels of anxiety and depression. Discussion: Currently, subjective instruments are used to evaluate the sleep pattern in cancer patients, since there is little information investigating the sleep disorders in these subjects. Recognizing these changes is fundamental as these symptoms can negatively affect the quality of life and their daytime performance.